Tick-borne pathogens Ehrlichia, Hepatozoon, and Babesia co-infection in owned dogs in Central Thailand - Chamsai, Tatiyanuch; Saechin, Aeknarin; Mongkolphan, Chalisa; Sariya, Ladawan; Tangsudjai, Siriporn (Frontiers in Veterinary Science, 2024)
Tick-borne pathogens are transmitted by a wide range of tick species and affect both human and animal health. Understanding the diversity of these pathogens and their co-infection rates in domesticated animals in urban areas is crucial for effective disease management and prevention. In this study, a total of 565 owned dogs in the central region of Thailand were investigated for the infection rate of three genera of Ehrlichia, Hepatozoon, and Babesia infection using multiplex PCR. The results revealed an overall infection rate of 19.1%, withEhrlichia having the highest infection rate (12.2%), followed by Babesia (2.5%) and Hepatozoon (1.4%). The rate of co-infection was 3%, with mixed infections involving two or three genera.Male dogs exhibited a slightly higher infection rate compared to females, although not statistically significant. Young adult dogs (1-3 years) showed the highest infection rate of both single infections and co-infections. Monthly infection rate indicated variations throughout the year, with co-infection rate significantly associated with overall infection rate. Clinical manifestations in three genera of infected dogs included thrombocytopenia and eosinopenia. The results of this study are useful to design strategies for the management and prevention of tickborne diseases in the study area.